Building Work Spirit: Analysis of the Work Environment, Workload and Co-Workers (Study Literature) - Hermawan, Eric (Dinasti Publisher, 2021)
Article Literature Review Building Work spirit: Analysis of the Work Environment, Workload and Colleagues is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in future research, within the scope of science Human Resource Management. The method of writing this Literature Review article is by the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) The Work Environment affects Work spirit; 2) Workload affects Work spirit; and 3) Colleagues affect Work spirit. Apart from these 3 exogenous variables that affect the endogenous variables of Work spirit, there are many other factors including the variables compensation, leadership and company loyalty.